2015 Information Theory and Applications Workshop (ITA) 2015
DOI: 10.1109/ita.2015.7308971
|View full text |Cite
|
Sign up to set email alerts
|

Channel estimation and hybrid combining for mmWave: Phase shifters or switches?

Abstract: Precodinglcombining and large antenna arra y s are essential in millimeter wave (mmWave) s y stems. In traditional MIMO s y stems, precodinglcombining is usuall y done digitall y at baseband with one radio frequenc y (RF) chain and one analog-to-digital converter (ADC) per antenna. The high cost and power consumption of RF chains and ADCs at mmWave frequencies make an all-digital processing approach prohibitive.When onl y a limited number of RF chains is available, h y brid architectures that split the precodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
176
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(178 citation statements)
references
References 30 publications
2
176
0
Order By: Relevance
“…In [8], it is shown that a HY beamformer with a number of RF chains that is twice the number of transmitted data streams may exactly mimic a FD beamformer; the analysis, which neglects energy efficiency issues, is however limited to either a single-user MIMO system or a MU-MIMO system with single-antenna receivers. The paper [9] proposes a new low-complexity post-coding structure, based on switches rather than on analog phase shifters; the performance of this new structure is evaluated in a rather simple scenario, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [8], it is shown that a HY beamformer with a number of RF chains that is twice the number of transmitted data streams may exactly mimic a FD beamformer; the analysis, which neglects energy efficiency issues, is however limited to either a single-user MIMO system or a MU-MIMO system with single-antenna receivers. The paper [9] proposes a new low-complexity post-coding structure, based on switches rather than on analog phase shifters; the performance of this new structure is evaluated in a rather simple scenario, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The paper also proposed extensions to the considered scenario recently proposed beamforming structures such as the one based on switches [9] and the one based on fixed phase shifters and switches [10]. Putting emphasis on the large number of antennas regime, asymptotic formulas of the ASE and of the GEE are derived with reference to some of these combining structures.…”
Section: Introductionmentioning
confidence: 99%
“…MMV problems derive from many applications areas, such as magnetoencephalography, which is a modality for imaging the brain [13]. Similar conceptions were also developed in the context of array processing [14,15] equalization of sparse communication channels [16,17], and more recently line spectrum denoising [18] and cognitive radio communications [19]. In this paper, we want to incorporate this fast growing field into SAR imaging applications.…”
Section: Introductionmentioning
confidence: 98%
“…However, one RF chain per antenna is impractical because the involved power consumption and the hardware cost are too high. To exploit the MIMO gain under a reasonable cost, one promising solution is to deploy hybrid analog-digital precoding schemes, realized using phase shifters or switches in the RF domain [3], and digital precoding schemes, implemented in the digital baseband domain as in conventional MIMO. If analog precoding is achieved using phase shifters only, the analog precoding matrix should have only constant modulus entries [4], [5], [6].…”
Section: Introductionmentioning
confidence: 99%
“…When a frequencyflat channel is considered, in [5] an adaptive compressed sensing (CS) based channel estimation algorithm is proposed to estimate the channel of a hybrid analog-digital massive MIMO system. This CS based channel estimation algorithm has been further extended in [9] by involving multiple measurement vectors (MMV) to improve the channel estimation accuracy. An adaptive multi-grid sparse recovery approach is applied in [10].…”
Section: Introductionmentioning
confidence: 99%